"It's never too late": Adult students and music learning in one online and offline convergent community music school. (February 2020) - Bayley, Jonathan G.; Waldron, Janice
This study is the third and final part of a longitudinal ethnographic investigation of music learning and teaching of the Online Academy of Irish Music (OAIM), an Irish music "school" situated in both online (www.oaim.ie ) and offline (Doolin, County Clare, Ireland) contexts. We first examined the online OAIM through teacher narratives in 2011. In the second part of the study, we explored the OAIM through students' perspectives at the OAIM's first offline Irish flute summer school retreat week in July 2013. In this third part and final part of the study, we attended the OAIM's offline tin whistle school week in October 2015 in Ennis, Ireland. The purpose of this part of the study was to continue our investigation of adult music learners who learned Celtic music through the OAIM, as it has continued to evolve as an online and offline convergent community music school. Findings indicate that the adult participants benefited from learning music through a combination of aural/oral, observational, and written notation in both online and offline contexts, but had differing perspectives as to what worked for them and what did not. As an online and offline convergent school, the OAIM offers an intriguing model of music learning and teaching for school music contexts and community music schools.